Activity of several kinds of drugs against Neospora caninum. Issue 6 (December 2015) - Qian, Weifeng; Wang, Hui; Shan, Dan; Li, Bo; Liu, Jing; Liu, Qun
Abstract: Neosporosis caused by Neospora caninum is a serious disease in cattle and dogs worldwide. It is the major cause of abortion and neonatal mortality in cattle. In this study, we evaluated the anti- N. caninum activity of Chinese medicine extracts (curcumin, artemether), herbicides (atrazine, glyphosate), anticoccidiosis drugs (toltrazuril and ponazuril), cyclophosphamide, diminazene aceturate and praziquantel in vitro using parasite growth, replication and host cell invasion assays in human foreskin fibroblast cultures. Curcumin, artemether, atrazine, toltrazuril and ponazuril exhibited inhibitory activity with 50% growth inhibitory concentration (IC50 ) of 1.1 ± 0.4, 1.0 ± 0.05, 11.2 ± 2.7, 30.3 ± 2.0 and 33.3 ± 4.1 μg/ml, respectively, in the growth inhibition assay. They were also active against protozoa replication, but only curcumin was effective against host cell invasion. Glyphosate, cyclophosphamide, diminazene aceturate and praziquantel were ineffective. In an in vivo infection model, curcumin showed no activity against N. caninum infection. We showed that curcumin, artemether, atrazine, toltrazuril, and ponazuril exhibited anti- N. caninum activity in vitro, providing important information for further studies on anti- N. caninum drugs. Graphical abstract: Highlights: We evaluated the anti- N. caninum activity of 9 drugs. Curcumin was effective against N. caninum in vitro, but not in mice. Curcumin was active against N. caninum replication and cell invasion. Atrazine, toltrazuril, ponazuril were only active against N. caninum replication.